Traumatic brain injury and occupational risk of low-level blast exposure on adverse career outcomes: an examination of administrative and medical separations from Service (2005–2015) - Belding, Jennifer N.; Bonkowski, James; Englert, Robyn (Frontiers in Neurology, 2024)
Introduction Although traumatic brain injury (TBI) has been linked with adverse long-term health, less research has examined whether TBI is linked with non-clinical outcomes including involuntary job loss. Symptoms associated with TBI may influence one’s ability to maintain gainful employment including employment in the U.S. military. That influence may impact military service members with exposure to repetitive low-level blast (LLB). Understanding the association between TBI and involuntary job loss outcomes among military populations is particularly important as it may be associated with differences in eligibility for post-service benefits. The purpose of the present research was to determine whether (1) TBI and related conditions are associated with involuntary job loss (i.e., medical and administrative separations from service) among military personnel, and (2) occupational risk of LLB is associated with involuntary job loss in both the presence and absence of clinical diagnoses of TBI and related conditions. Method This research leveraged population-level data from the Career History Archival Medical and Personnel System for enlisted personnel who served on active duty between 2005–2015. Risk of LLB exposure was categorized using military occupational specialty as a proxy. Medical diagnoses were identified using ICD-9 codes. Separations for medical and administrative reasons were identified. Results Risk for administrative separation differed across medical diagnoses of interest, but those who worked in high-risk occupations were more likely to be administratively separated than those working in low-risk occupations. Risk for medical separation was associated with occupational risk of LLB and each of the diagnoses of interest, though significant interactions suggested that the effects of certain diagnoses of interest (e.g., concussion, cognitive problems, postconcussive syndrome, migraines) on medical separations was greater among those working in high-risk occupations. Discussion Taken together, the present research suggests that TBI and associated medical conditions, as well as occupational risk of LLB, are associated with long-term involuntary job loss for medical reasons. This study is the first to demonstrate involuntary military job loss outcomes associated with TBI, mental health conditions, and conditions associated with blast exposure using both inpatient and outpatient population-level data and may have important implications for civilian employment and post-service benefits.